Dermatomyositis complicating penicillamine treatment. - Fernandes, L (1977)
A case of dermatomyositis developing during the course of treatment with D-penicillamine in a patient with rheumatoid arthritis is described. Complete remission occurred on withdrawal of the drug. Possible alternative diagnoses are discussed.